Quality of Life Chronic Kidney Disease Patients Undergoing Continuous Ambulatory Peritoneal Dialysis at Hermina Hospital Bekasi Reviews from Medical Science and Islam - Tasya Anita Salam; Linda Armelia; Muhammad Arsyad (Junior Medical Journal, 2022)
According to Risdeskes (2018), the percentage of chronic diseases (CKD) has increased after previously being 2% to 3.8% of the total population of Indonesia. Abnormalities of kidney structure and function can be measured by a glomerular filtration rate (GFR) of less than 60 ml/minute/1.73 m² for a period of three months or more. Renal replacement therapy (TPG) in the form of peritoneal dialysis is an alternative way to maintain kidney function in CKD conditions. Treatment of patients undergoing peritoneal dialysis does not only focus on technical aspects but also psychosocial factors, namely the quality of life that will affect the patient's health. Therefore, it is important to know the quality of life of CKD patients undergoing continuous ambulatory peritoneal dialysis (CAPD) in terms of medical science and Islamic views. The type of research used is descriptive observational through a cross sectional approach using the SF-36 questionnaire which has been validated in uniting health. The population in this study were patients who underwent CAPD therapy at Hermina Hospital Bekasi. The results showed that of 45 respondents, most of whom were male with a history of hypertension and had undergone CAPD therapy for 1-3 years, the average score of quality of life score of respondents was 52, which was categorized as not good(60). It is influenced by physical function, physical limitations, vitality, mental limitations, and mental health. ). In the Islamic view, CAPD therapy is allowed to be carried out because this therapy is a form of endeavor that aims to maintain life for CKD patients.